Beyond 'Navel-Gazing' and 'Mush': Learning about Identity in Australian Classrooms. (March 2013) - Brett, Peter
This article explores how teaching about identity in Australia has been framed by the recent historical and political context. It analyses the influential characterisation of Australian identity during John Howard's period in office between 1996 and 2007. The findings of Australian education researchers relating to young people's sense of what it means to be Australian are reviewed. The author goes on to discuss the curriculum content, language, and underpinning intellectual frameworks of key areas of the emerging Australian Curriculum. Methodologically, the article draws upon the tools of critical policy and discourse analysis. The History, Geography, Civics and Citizenship curricula and related cross-curricular priorities are analysed in relation to their articulation of learning about identity. Some conclusions are drawn as to how Australian teachers can best be supported to address issues relating to identity in their school contexts. The author argues that teachers need help in developing the skills and confidence to see the emerging Australian Curriculum as a framework and not a straitjacket which prevents them from exploring unarticulated identity issues. He further concludes that there need to be curriculum opportunities to explore the political dimensions of identity issues in critical and participative ways.